2006
DOI: 10.1001/archpedi.160.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Parental Media Mediation Styles for Children Aged 2 to 11 Years

Abstract: Pediatric health care providers should identify parental practices and reinforce active media mediation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
3
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 30 publications
8
91
3
9
Order By: Relevance
“…In the modality of children's use of internet and other media, families are playing an important role. Parents' knowledge about the risks of abusing media tools is the most determining factor for the prevention of addiction (34). While there are studies that, similar to our results, did not find a correlation between the parents' level of education and IA (13,33), there are other studies that found a lower education level of fathers in IA cases (35) or established a high paternal education level as a risk factor for IA (36).…”
Section: Discussionsupporting
confidence: 81%
“…In the modality of children's use of internet and other media, families are playing an important role. Parents' knowledge about the risks of abusing media tools is the most determining factor for the prevention of addiction (34). While there are studies that, similar to our results, did not find a correlation between the parents' level of education and IA (13,33), there are other studies that found a lower education level of fathers in IA cases (35) or established a high paternal education level as a risk factor for IA (36).…”
Section: Discussionsupporting
confidence: 81%
“…Although restrictive TV parenting practices were associated with greater sedentary time and less MVPA in this sample, several studies have demonstrated that restrictive TV parenting practices were associated with less TV viewing among children, 10,14,15 which is, in itself, a desirable outcome; however, this was not assessed in this study. Some TV reduction interventions have successfully improved children's weight status, 31,32 and this effect was mediated by children's dietary intake in one of the studies, 31 suggesting that TV reduction is important for obesity prevention and treatment initiatives.…”
Section: Discussioncontrasting
confidence: 57%
“…10,14,15 Varied definitions and instruments have been used to assess PA parenting practices through child 16 or parent report. 9,17,18 Some of these instruments included restriction of screen media (TV viewing, computer, and videogame playing), particularly TV viewing, as a major part of the scale 18 or as a subfactor of the scale.…”
mentioning
confidence: 99%
“…Bu bağlamda Şubatlı, Akgöngür, Öztürk, Uruş, & Aydoğdu (2006) tarafından yapılan bir araştırmada çocukların izledikleri filmlerin kahramanlarına öykündükleri ve okulda akran grupları içerisinde söz konusu film kahramanlarına özgü tavır ve dil geliştirdikleri bulgusu elde edilmiştir. Barkin, Ip, Richardson, Klinepeter, Finch & Krcmar (2006), ebeveynlerin medyanın yanlış kullanımının içerdiği riskleri bilmelerinin bu konuda alınacak önlemler için en önemli belirleyici faktör olduğunu belirtmişlerdir.…”
Section: Kitle İletişim Araçlarıunclassified